Regulatory Challenges and Shifting Domestic Investment Behaviour in Indonesia: A Legal and Economic Analysis Towards Golden Indonesia 2045 - Agus Sudarya; Yuyut Prayuti (Journal of Law, Politic and Humanities, 2025)
Indonesia’s economic transformation toward Golden Indonesia 2045 demands a robust and sustainable investment climate supported by regulatory and institutional resilience. While foreign direct investment has expanded significantly, domestic investment behaviour remains shaped by macroeconomic and legal constraints. This study employs a normative legal and qualitative analysis, supported by doctrinal and comparative approaches. It examines primary legal sources—including Law No. 25 of 2007 on Investment and Law No. 37 of 2004 on Bankruptcy—alongside secondary literature and empirical data on domestic investment determinants. Findings reveal that domestic investor behaviour is increasingly influenced by human development, labour quality, infrastructure, and inflation stability. However, Indonesia’s legal framework does not adequately support business continuity. The absence of insolvency testing and overly creditor-centric bankruptcy procedures create high investment risks. Strengthening regulatory mechanisms through insolvency reform, going concern protection, and better alignment with international best practices is essential for promoting sustainable domestic investment. Legal reforms would foster resilience, encourage long-term capital flows, and strengthen Indonesia’s economic position toward 2045.